Need Analysis of Electrodes for Shielded Metal Arc Welding in 3G Position at the Fabrication Laboratory/ Analisis Kebutuhan Elektroda pada Pengelasan Model Shielded Metal Arc Welding Posisi 3G di Laboratorium Fabrikasi - Muntaha Muntaha (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2021)
The Shielded Metal Arc Welding (SMAW) practicum in the 3G position is a mandatory practicum course for students of the Mechanical Engineering Education Department. This welding capability requires a thick strip of plate material and a lot of electrodes so that large funds are needed. The purpose of this research is to analyze the need for effectively wrapped electrode consumables that are needed by students in completing the SMAW welding assignment in a 3G position and how long it can be done with 3G welding competence. This study uses descriptive analysis techniques, both quantitatively and qualitatively, with the population studied being students of Mechanical Engineering Education, Yogyakarta State University. Samples were taken by students who practice SMAW welding fabrication courses. The results of the study of the need for electrodes on the welding capability of SMA W 3 G position for the manufacture of fillers require 4 pieces of American Welding Society (AWS) E701 6 electrodes with a diameter of 2,6 mm and for making covers requires AWS E7018 electrodes with a diameter of 3,2 mm in the amount of 5 pieces. Graduates from high schools need a longer time of 136 minutes compared to SMKs which only require 75. Abstrak Praktikum pengelasan Shielded Metal Arc Welding Welding (SMAW) pada posisi 3G merupakan mata kuliah praktikum wajib bagi mahasiswa Jurusan Pendidikan Teknik Mesin. Pengelasan ini memerlukan bahan plat strip yang tebal dan elektroda yang banyak sehingga membutuhkan dana yang besar. Tujuan penelitian ini adalah menganalisa kebutuhan elektroda terbungkus yang efektif dibutuhkan mahasiswa dalam tugas pengelasan SMAW pada posisi 3G dan berapa lama bisa di kerjakan dengan kompetensi pengelasan 3G. penelitian ini mempergunakan Teknik analisis deskriptif, baik secara kuantatif maupun dengan populasi yang diteliti mahasiswa Pendidikan Teknik Mesin Universitas Negeri Yogyakarta. Sampel yang diambil mahasiswa yang praktek mata kuliah Fabrikasi pengelasan SMAW. Hasil penelitian kebutuhan elektroda terhadap kemampuan pengelasan SMAW posisi 3G untuk pembuatan filler membutuhkan elektroda American Welding Society (AWS) E7016 diameter 2,6 mm sebanyak 4 buah dan untuk membuat cover membutuhkan elektroda AWS 7018 diameter 3,2 mm sebanyak 5 buah. Lulusan dari SMA memerlukan waktu yang lebih lama sebesar 136 menit di bandingkan dari SMK yang hanya membutuhkan waktu 75 menit.